Are comparable studies really comparable? Suggestions from a problem-solving experiment on urban and rural great tits - Ernő Vincze; Ineta Kačergytė; Juliane Gaviraghi Mussoi; Utku Urhan; Anders Brodin (Animal Cognition)
Abstract Performance in tests of various cognitive abilities has often been compared, both within and between species. In intraspecific comparisons, habitat effects on cognition has been a popular topic, frequently with an underlying assumption that urban animals should perform better than their rural conspecifics. In this study, we tested problem-solving ability in great tits Parus major, in a string-pulling and a plug-opening test. Our aim was to compare performance between urban and rural great tits, and to compare their performance with previously published problem solving studies. Our great tits perfomed better in string-pulling than their conspecifics in previous studies (solving success: 54%), and better than their close relative, the mountain chickadee Poecile gambeli, in the plug-opening test (solving success: 70%). Solving latency became shorter over four repeated sessions, indicating learning abilities, and showed among-individual correlation between the two tests. However, the solving ability did not differ between habitat types in either test. Somewhat unexpectedly, we found marked differences between study years even though we tried to keep conditions identical. These were probably due to small changes to the experimental protocol between years, for example the unavoidable changes of observers and changes in the size and material of test devices. This has an important implication: if small changes in an otherwise identical set-up can have strong effects, meaningful comparisons of cognitive performance between different labs must be extremely hard. In a wider perspective this highlights the replicability problem often present in animal behaviour studies.